-8(x+3)=-8x-5(x+1)

Simple and best practice solution for -8(x+3)=-8x-5(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8(x+3)=-8x-5(x+1) equation:


Simplifying
-8(x + 3) = -8x + -5(x + 1)

Reorder the terms:
-8(3 + x) = -8x + -5(x + 1)
(3 * -8 + x * -8) = -8x + -5(x + 1)
(-24 + -8x) = -8x + -5(x + 1)

Reorder the terms:
-24 + -8x = -8x + -5(1 + x)
-24 + -8x = -8x + (1 * -5 + x * -5)
-24 + -8x = -8x + (-5 + -5x)

Reorder the terms:
-24 + -8x = -5 + -8x + -5x

Combine like terms: -8x + -5x = -13x
-24 + -8x = -5 + -13x

Solving
-24 + -8x = -5 + -13x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '13x' to each side of the equation.
-24 + -8x + 13x = -5 + -13x + 13x

Combine like terms: -8x + 13x = 5x
-24 + 5x = -5 + -13x + 13x

Combine like terms: -13x + 13x = 0
-24 + 5x = -5 + 0
-24 + 5x = -5

Add '24' to each side of the equation.
-24 + 24 + 5x = -5 + 24

Combine like terms: -24 + 24 = 0
0 + 5x = -5 + 24
5x = -5 + 24

Combine like terms: -5 + 24 = 19
5x = 19

Divide each side by '5'.
x = 3.8

Simplifying
x = 3.8

See similar equations:

| 3x^2-10x-75=0 | | (p+15)+(2p-24)+p=479 | | (4x^2)-33x+63=0 | | 0=3x^2-24x+12 | | y=3x^2-24x+12 | | 9x+15=16x^2 | | 18+3x=24+3x | | 9x+15-16x^2=0 | | 2x^2-5=-4.5 | | -16x^2-29x+4=16 | | 12t^2-22t-20=0 | | 4x^3+4x^2+x=0 | | 6x+8-2x(7-27)=2(6+1) | | 3c+2-5c=-c+3 | | (4/5)b=12 | | 9x^2-35=14 | | 107-5x^2=-18 | | 107-5x^2=18 | | -7v-1=-4(v+7) | | 4(y+7)=-7y-27 | | 3(x-7)=y | | 5x^3-2x^2-10x+4= | | 3z+2z=25-2i | | -2w+10=6(w-9) | | 10=9x-7 | | 3x^2+4y^2-6x-32y+55=0 | | 16x^3-25x=0 | | 6x-3y+18=0 | | 6-x=-10 | | 5x+16y-12z=230 | | 2y-4x-12=0 | | 10x+24y=123 |

Equations solver categories